SPECIAL GUARANTEES FOR PREGNANT WOMEN ARE NOT DISCRIMINATION IN LABOUR RELATIONS - Raximov Miryoqub Aktamovich (Galaxy International Interdisciplinary Research Journal, 2023)
According to the statistical agency, the number of labor resources in the Republic of Uzbekistan in 2022 was 19494 thousand people, which increased by 0.8 percent when compared with the corresponding period of the previous year. It should be noted that, among them there are also pregnant women who carry out their labor activity. So, what guarantees does the new Labor Code provide to employees of this category? We will try to answer these questions below.